2010
DOI: 10.1016/j.agee.2010.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changed grazing regimes and habitat fragmentation on Mediterranean grassland birds

Abstract: In Iberian cereal-steppes, decoupling of payments from current production levels through the Single Farm Payment raised concerns regarding the potential for land abandonment and replacement of sheep by cattle, with eventual negative consequences for declining grassland birds. This study addressed this issue by analysing the responses of five grassland bird species of conservation concern to spatial land use gradients, which are expected to reflect changes potentially associated with the CAP reform. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 26 publications
3
40
1
Order By: Relevance
“…Non-lethal effects may also be relevant (Cresswell, 2008), as perceived predation risk may induce individuals to avoid breeding or foraging near wooded edges and in small patches (Ribic et al, 2009 and references therein), thereby causing reductions in the amount of usable habitat that are much larger than the area effectively occupied by forest plantations ). However, although some species of conservation concern show avoidance of forest edges (Stroud et al, 1990;, others may show no avoidance or even preference for this habitat type (Avery, 1989;Reino et al, 2009Reino et al, , 2010. Also, while many studies have documented increased predation rates at habitat edges (review in Batáry and Báldi, 2004), such an effect was not found by studies focusing specifically on forest plantations .…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Non-lethal effects may also be relevant (Cresswell, 2008), as perceived predation risk may induce individuals to avoid breeding or foraging near wooded edges and in small patches (Ribic et al, 2009 and references therein), thereby causing reductions in the amount of usable habitat that are much larger than the area effectively occupied by forest plantations ). However, although some species of conservation concern show avoidance of forest edges (Stroud et al, 1990;, others may show no avoidance or even preference for this habitat type (Avery, 1989;Reino et al, 2009Reino et al, , 2010. Also, while many studies have documented increased predation rates at habitat edges (review in Batáry and Báldi, 2004), such an effect was not found by studies focusing specifically on forest plantations .…”
Section: Introductionmentioning
confidence: 72%
“…The study focused on fallow fields, because they are particularly important for grassland birds (Delgado and Moreira, 2000;Reino et al, 2010), and to reduce variation among sites unrelated to forest and landscape features . Sampling sites were selected according to Reino et al (2009), involving the identification of all forest plantations from land cover maps (http:// www.igeo.pt/IGEO/portugues/produtos/inf cartografica.htm) and systematic field surveys.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural intensification and land abandonment represent an important threat for farmland wildlife in southern Europe (Bignal & McCracken 1996, Pain & Pienkowski 1997, Aebischer & Lucio 1997, Meriggi & Mazzoni della Stella 2004). According to Reino et al (2010) the same agricultural policies may be favourable for some species of conservation concern but detrimental to other farmland birds. Consequently, they cannot be assumed to bring uniform conservation and management benefits (Suárez-Seoane et al 2002, Báldi et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…AES were introduced into EU law in the 1980s, and although designed primarily as a production control measure, they rapidly became the most important support to biodiversity in agro-ecosystems across the whole Europe (Whittingham, 2007). Depending on the species and landscape studied, AES were successful for some species and neutral for others (Batáry et al, 2011;Broyer et al, 2014;Reino et al, 2010), or even had negative effects (6% of cases reviewed in Kleijn and Sutherland, 2003). Nonetheless, Kleijn and Sutherland (2003) found a positive response for biodiversity in the 54% of cases reviewed across Europe, as well as many recent studies on plant and animal diversity did (e.g.…”
Section: Introductionmentioning
confidence: 99%